ANALISIS KESULITAN PENGGUNAAN MICROSOFT TEAMS PADA PEMBELAJARAN MATEMATIKA DIMASA PANDEMI COVID-19 - Muhamad Ruslan Layn; Arie Anang Setyo (JOEL: Journal of Educational and Language Research, 2022)
The world is currently faced with a covid-19 pandemic that forces people to move at home, including the world of education that carries out teaching and learning activities from home using online learning. This research aims to find out the causes and ways to overcome the learning difficulties of students of class X MIPA 4 Sma Negeri 1 Kota Sorong on math learning using microsoft teams during the covid-19 pandemic. This type of research is quantitative descriptive combined with qualitative approaches. The subjects of this study were students of class X MIPA 4 Sma Negeri 1 Kota Sorong school year 2020/2021 which amounted to 26 students and 1 math teacher. The object in this study is the cause of students' learning difficulties using microsoft teams on math learning provided by teachers. Data collection techniques are observation, questionnaire, interview and documentation. The data analysis techniques in this study are qualitative and quantitative. The results showed that students experienced several causes of learning difficulties that were divided into 4 (four) indicators, students' inability to learn online, interaction in the learning process, assignments and teaching materials and technical constraints on online learning using microsoft teams.